1999
DOI: 10.1055/s-1999-69
|View full text |Cite
|
Sign up to set email alerts
|

9. Appropriateness of Colonoscopy: Lower Abdominal Pain or Constipation 1

Abstract: This article presents a literature review on lower abdominal pain and change in bowel habits, that was provided to the panelists to study and comment prior to the panel meeting to support their ratings of appropriateness of use of colo noscopy. This article furthermore presents an overview of the main panel results related to abdominal pain and change in bowel habits (mainly constipation) and a sum mary of published evidence and panel-based appropriate ness criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…46 Previous studies on diagnostic colonoscopy for nonbleeding symptoms mostly have shown low yields, 47 but, again, very few studies have focused on young patients. 48 In a large, German study, the prevalence of advanced neoplasia was only 2.0% in the subset of patients aged !50 years. 16 However, this study, which included many patients with family histories of CRC, was based on an administrative database that did not contain details on each symptom.…”
Section: Discussionmentioning
confidence: 99%
“…46 Previous studies on diagnostic colonoscopy for nonbleeding symptoms mostly have shown low yields, 47 but, again, very few studies have focused on young patients. 48 In a large, German study, the prevalence of advanced neoplasia was only 2.0% in the subset of patients aged !50 years. 16 However, this study, which included many patients with family histories of CRC, was based on an administrative database that did not contain details on each symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our findings are still supportive and consistent with the ASGE guidelines, of moderate quality of evidence, for the role of endoscopy in constipation. That being, that GI endoscopy should not be performed in the initial evaluation of patients presenting with symptoms of chronic constipation in the absence of alarm features or suspicion of organic GI disease [1]. Also, when comparing EGD/Colonoscopy together with Colonoscopy alone, the diagnostic yield was higher for anatomic findings.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines for gastroendotology were developed in line with international guidelines from [20][21][22][23][24][25][26][27]. The themes covered were chronic diarrhea, gastroesophageal reflux disease, abdominal pain, anemia/blood in feces, inflammatory bowel disease and colorectal cancer.…”
Section: The Hospital Casementioning
confidence: 99%